GIFT GIVING BEHAVIOR AMONG MILLENNIALS, THE USE OF PHOTO ELICITATION INTERVIEW TO DISCOVER CONSUMER INSIGHT - Rachmahani, Hera; Kusumasondjaja, Sony (UI Scholars Hub, 2021)
Manuscript type: Research paper Research Aims: This paper aims to explore gift-giving activities among millennials at the perspective of gift-giver using the photo elicitation interview. The typology of the relationship between gift givers and recieversand the effects of this relationship to the types of products given in gift-giving activities are also evaluated. Design/methodology/approach: This paper is using phenomenological approach and photo elicitation interview with purposive convenience sampling method to obtain gift-givers decision making process in searching gift products. Research Findings: The process of searching, preparing, and delivering of gifts is influenced by several factors, namely the closeness of the relationship, past experiences and the moment of giving the gift. The structure of intimacy creates hierarchy of gift giving given by gift givers. The position and social class of the gift receiver affect the shape, price, and gifts delivery process. Theoretical Contribution/Originality: This research is expected to provide an understanding of the consumer decision-making process in giving gifts at certain moments experienced by consumers. Practitioner/Policy Implication: This paper give insights to the practitioner about the promotional and products design that are associated with the closeness between consumers and gift givers to attract gift-givers giving a gift to the special people around them This study is only discuss gift-giving behavior from gift-givers and does not pay attention to the recipient perspective so it is less comprehensive in discussing gift-giving behavior in the millennial generation